Factors contributing to the subjective career success among Islamic educators in primary schools - Supa'ad, Mesnan; Abdul Wahat, Nor Wahiza; Mohd Fakhruddin, Fathiyah; Suandi, Turiman (Australian International Academic Centre, 2013)
A very limited research has been done in the field of career development among Islamic education teachers. Most of the previous researches showed an improvement in terms of grades, positions, and responsibilities of their previous routines as an indicator of their career advancement. However, this conceptual (concept paper) discusses how personality factors, career planning, and career strategy can provide significant contribution to the success of Islamic education teachers’ career. Based on the Five Factor Model, Gould Planning Model, and the support of previous researches, this paper discusses how these three factors can contribute to the success of Islamic education teachers’ career. This paper also discusses its impact towards Islamic education teachers in Malaysia, schools management, District Education Office, Ministry of Education, and teachers education institutions.